Screening of Rice Germplasm with Physiological Traits for Identification of Heat Tolerant Genotypes - Veronica, N.; Rani, Y. Ashoka; Subrahmanyam, D.; Rao, K. L. N.; Ahamad, M. Lal; Rani, P. Prasuna; Yugandhar, P.; Voleti, S. R. (International Journal of Bio-resource and Stress Management, 2019)
High temperature as a part of the climate change scenario is imposing a severe threat to rice production and productivity worldwide. Field experiment was conducted in ICAR-IIRR during rabi 2016-17 to screen 60 diverse rice genotypes comprising of 2 germplasm lines, 11 green super rice lines, 2 introgression lines, 8 landraces, 2 tropical japonicas and 35 released varieties including 2 checks for identification of high temperature tolerant genotypes. They were tested for their nature of thermotolerance using cell membrane thermostability, PSII activity (Fv/Fm) and paraquat tolerance test as screening criteria. There was a reduction in all the above measured traits in all the genotypes however, among the genotypes the extent of reduction varied. Among the genotypes screened, Rasi, Akshayadhan, HKR47, IR64, Assanchidiya had recorded a higher grain yield under high temperature conditions and hence could be categorized as heat tolerant whereas ADT43, Vandana, NDR359 MTU1001 and IR36 had lower yields and hence were categorized as heat susceptible. The screening traits were correlated with grain yield recorded under high temperature. Positive and significant association was noted between cell membrane thermostability, Fv/Fm measured under high temperature stress with the grain yield. The tolerant genotypes also had a higher cell membrane thermostability and higher Fv/Fmunder high temperature conditions. Among the analysed traits, it can be concluded that CMS and Fv/Fm can be used efficiently to screen the germplasm for thermotolerance.